Changing “portrait” of patients with newly diagnosed idiopathic pulmonary hypertension over the past two decades - A. M. Shariya; T. V. Martynyuk (Евразийский Кардиологический Журнал, 2024)
Objective: to perform a comprehensive analysis of the clinical, functional and hemodynamic status of patients with idiopathic pulmonary hypertension (IPAH) to compare the "portrait" of historical and modern subgroups.   Materials and methods. The study included 120 patients with IPAH observed in the Department of Pulmonary Hypertension and Heart Diseases, E.I. Chazov National Medical Research Center of Cardiology. The pts were divided into 2 subgroups depending on the time of diagnosis and were comparable in terms of the initial functional class (WHO). A comparative analysis of clinical, functional, and hemodynamic parameters was carried out. The diagnosis was established according to the algorithm of the Eurasian (2019) and Russian guidelines for the diagnosis and treatment of pulmonary hypertension (PH) (2020).   Results. The median time from the onset of PH symptoms to diagnosis in the historical and modern cohorts was 24 months and 13.5 months, respectively, and from the first visit to the diagnosis of IPAH – 13 months and 3.5 months. The median age of patients was 31 years and 40.5 years. In both subgroups, the number of women dominated – up to 86.6 % of patients in the modern cohort. Clinical, laboratory, functional and instrumental tests did not differ significantly between the subgroups. In the structure of concomitant pathology, comorbidity with cardiovascular pathology is most common, in a larger percentage in the modern cohort of patients: hypertension – up to 31.6 %, obesity – up to 25 % and diabetes mellitus – up to 5 %. According to various risk assessment scales, most patients in both subgroups demonstrated intermediate risk at the time of diagnosis, but in the modern cohort, a large proportion of high-risk patients was noted (20.0 %).   Conclusion. Nowadays, IPAH remains a late-diagnosed disease, which contributes to a later treatment prescription. The clinical "portrait" of patients with IPAH has changed over the years towards older and more comorbid patients, especially with cardiovascular diseases. Timely detection and treatment of concomitant pathology, timely risk assessment are the key to prescribing the most effective treatment regimens, improving the quality of life and prognosis of patients with IPAH.